Engineering mechanics of solids - Popov, E. P. (Egor Paul) 1913- (Prentice-Hall international series in civil engineering and engineering mechanics, 1990)
This book presents a comprehensive, cross-referenced examination of engineering mechanics of solids. Traditional topics are supplemented by several newly-emerging disciplines, such as the probabilistic basis for structural analysis, and matrix methods. Although retaining its character as a complete traditional book on mechanics of solids with advanced overtones from the first edition, the second edition of Engineering Mechanics of Solids has been significantly revised. The book reflects an emphasis on the SI system of units and presents a simpler approach for calculations of axial stress that provides a more obvious, intuitive approach. It also now includes a greater number of chapters as well as an expanded chapter on Mechanical Properties of Materials and introduces a number of avant-garde topics. Among these topics are an advanced analytic expression for cyclic loading and a novel failure surface for brittle material. An essential reference book for civil, mechanical, and aeronautical engineers.